TYRO3 as a molecular target for growth inhibition and apoptosis induction in bladder cancer - Dufour, Florent (Br J Cancer, 2019)
BACKGROUND: Muscle-invasive bladder cancer (MIBC) is an aggressive neoplasm with poor prognosis, lacking effective therapeutic targets. Oncogenic dependency on members of the TAM tyrosine kinase receptor family (TYRO3, AXL, MERTK) has been reported in several cancer types, but their role in bladder cancer has never been explored. METHODS: TAM receptor expression was evaluated in two series of human bladder tumours by gene expression (TCGA and CIT series), immunohistochemistry and western blotting analyses (CIT series). The role of the different TAM receptors was assessed by loss-of-function experiments and pharmaceutical inhibition in vitro and in vivo. RESULTS: We reported a significantly higher expression of TYRO3, but not AXL or MERTK, in both non-MIBCs and MIBCs, compared to normal urothelium. Loss-of-function experiments identified a TYRO3-dependency of bladder carcinoma-derived cells both in vitro and in a mouse xenograft model, whereas AXL and MERTK depletion had only a minor impact on cell viability. Accordingly, TYRO3-dependent bladder tumour cells were sensitive to pharmacological treatment with two pan-TAM inhibitors. Finally, growth inhibition upon TYRO3 depletion relies on cell cycle inhibition and apoptosis associated with induction of tumour-suppressive signals. CONCLUSIONS: Our results provide a preclinical proof of concept for TYRO3 as a potential therapeutic target in bladder cancer.